2009
DOI: 10.1051/0004-6361/200911635
|View full text |Cite
|
Sign up to set email alerts
|

Formation of gaseous arms in barred galaxies with dynamically important magnetic field: 3D MHD simulations

Abstract: Aims. We present results of three-dimensional nonlinear MHD simulations of a large-scale magnetic field and its evolution inside a barred galaxy with the back reaction of the magnetic field on the gas. The model does not consider the dynamo process. To compare our modeling results with observations, we construct maps of the high-frequency (Faraday-rotation-free) polarized radio emission on the basis of simulated magnetic fields. The model accounts for the effects of projection and the limited resolution of rea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 14 publications
4
13
0
Order By: Relevance
“…The effect described above repeats and at the time step t = 1.68 Gyr magnetic arms again drift into the inter-arm region and form the doublering structure. The drift of the magnetic arms into the inter-arm area was described in our previous paper (Kulesza-Żydzik et al 2009), where we concluded that this behaviour is caused by the difference in the angular velocity of the magnetic arms and the gaseous spirals. Namely, the magnetic arms do not corotate with gaseous spiral structure, but follow the general gas motion in the disk, which has a slightly lower angular velocity.…”
Section: Time Evolution Of a Barred Galaxysupporting
confidence: 62%
See 3 more Smart Citations
“…The effect described above repeats and at the time step t = 1.68 Gyr magnetic arms again drift into the inter-arm region and form the doublering structure. The drift of the magnetic arms into the inter-arm area was described in our previous paper (Kulesza-Żydzik et al 2009), where we concluded that this behaviour is caused by the difference in the angular velocity of the magnetic arms and the gaseous spirals. Namely, the magnetic arms do not corotate with gaseous spiral structure, but follow the general gas motion in the disk, which has a slightly lower angular velocity.…”
Section: Time Evolution Of a Barred Galaxysupporting
confidence: 62%
“…However, they did not find the mechanism which is responsible for shifting of the magnetic arms from the gasoues ones to the inter-arm space. As we mentioned in the intorduction, the concept of the magnetic field drift into the inter-arm region was described earlier only in two papers (Otmianowska-Mazur et al 2002;Kulesza-Żydzik et al 2009). In the aforesaid paper the authours found this mechanism for the first time, but in those calculation they did not take into account the back-reaction of magnetic field to the gas, which could be crucial in these studies.…”
Section: Gas Dynamics In the Context Of Earlier Experimentsmentioning
confidence: 98%
See 2 more Smart Citations
“…The development of the magnetic field in barred galaxies was studied numerically by many authors (e.g. Otmianowska-Mazur et al 2002, Moss et al 2007, Kulesza-Żydzik et al 2009-Paper I, Kulesza-Żydzik et al 2010, however, the models including the classical dynamo theory in this calculations did not show the promising results (Moss et al 2007). In opposition to them in our two papers (Paper I & II) we presented numerical models which are capable to explain the drift of magnetic field arms into the interarm region.…”
Section: Introductionmentioning
confidence: 99%